Thermoluminescent dosimeters for low dose X-ray measurements. (January 2016) - Del Sol Fernández, S.; García-Salcedo, R.; Sánchez-Guzmán, D.; Ramírez-Rodríguez, G.; Gaona, E.; de León-Alfaro, M.A.; Rivera-Montalvo, T.
Abstract: The response of TLD-100, CaSO4 :Dy and LiF:Mg, Cu, P for a range of X-ray low dose was measured. For calibration, the TLDs were arranged at the center of the X-ray field. The dose output of the X-ray machine was determined using an ACCU-Gold. All dosimeters were exposed at the available air kerma values of 14.69 mGy within a field 10×10 cm 2 at 80 cm of SSD. Results of LiF:Mg, Cu, P X-ray irradiated showed 4.8 times higher sensitivity than TLD-100. Meanwhile, TL response of CaSO4 :Dy exposed at the same dose was 5.6 time higher than TLD-100. Experimental results show for low dose X-ray measurements a better linearity for LiF:Mg, Cu, P compared with that of TLD-100. CaSO4 :Dy showed a linearity from 0.1 to 60 mGy Highlights: Low dose X-ray doses for personal dosimetry were measured. Radiation dose (µGy ) for environmental dosimetry were determined. Scattering radiation dose were measured by TLDs. Linearity of pair TLD system was successful in the range of microgray. Pair TLDs composed by CaSO4 :Dy and by LiF:Mg, Cu, P. is suggested for clinical dosimetry.